Heaters for semiconductor manufacturing equipment

By adding yttrium aluminate phase to the AlN ceramic matrix of the heater for semiconductor manufacturing device and controlling the mass ratio of Ti/Ca, the problem of difficult control of the volume resistivity of the ceramic matrix is ​​solved, and high volume resistivity and strength at high temperatures are achieved.

CN114093792BActive Publication Date: 2025-03-25NGK INSULATORS LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202111371780.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-02-08
Filing Date
2018-07-02
Publication Date
2025-03-25
Estimated Expiration
2038-07-02

AI Technical Summary

Technical Problem

In the heaters for semiconductor manufacturing devices, the volume resistivity of the AlN ceramic matrix is ​​difficult to control, and it is easy to drop in high temperatures, resulting in damage to the wafer.

Method used

By adding yttrium aluminate phase as the crystalline phase to the AlN ceramic matrix, and controlling the mass ratio of Ti/Ca is 0.13 or more, the formation of TiN is avoided, thereby improving the volume resistivity of the ceramic matrix.

Benefits of technology

At high temperatures, the volume resistivity of the AlN ceramic matrix is ​​significantly improved, reducing the leakage current from the heating element to the wafer, and enhancing the strength and thermal conductivity of the ceramic matrix.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114093792B_ABST
    Figure CN114093792B_ABST
Patent Text Reader

Abstract

The present invention provides a heater for semiconductor manufacturing equipment, which is a heater for semiconductor manufacturing equipment with a heating element buried inside an AlN ceramic substrate, an RF electrode buried in the AlN ceramic substrate, the AlN ceramic substrate contains O, C, Ti, Ca, Y and an yttrium aluminate phase as a crystalline phase, and the mass ratio of Ti / Ca is greater than 0.13, and the Ti content of the AlN ceramic substrate is greater than 18 mass ppm and less than 95 mass ppm.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the invention application with application number 201880002671.8, application date July 2, 2018, and invention name “Heater for semiconductor manufacturing equipment”. Technical Field

[0002] The present invention relates to a heater for a semiconductor manufacturing device. Background Art

[0003] As a heater for semiconductor manufacturing equipment, there is known a heater for semiconductor manufacturing equipment having an AlN ceramic substrate and a heating element embedded in the AlN ceramic substrate as shown in Patent Document 1. Such a heater for semiconductor manufacturing equipment is used to heat a wafer placed on the surface of the AlN ceramic substrate. In addition, as a heater for semiconductor manufacturing equipment, there is known a heater for semiconductor manufacturing equipment having a heating element and an electrostatic electrode embedded in the AlN ceramic substrate as shown in Patent Document 2.

[0004] On the other hand, in Patent Documents 3 and 4, an AlN ceramic matrix is ​​disclosed as an AlN ceramic matrix obtained by mixing CaO, TiO2, etc. in a raw material and sintering. For example, Document 3 discloses an example in which 2 wt% of CaO and 0.5 wt% of TiO2 are mixed in the raw material (Ti / Ca mass ratio is 0.21), and Document 4 discloses an example in which 1 wt% of CaO and 0.2 wt% of TiO2 are mixed in the raw material (Ti / Ca mass ratio is 0.15).

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2008-153194

[0008] Patent Document 2: Japanese Patent Application Publication No. 2005-281046

[0009] Patent Document 3: Japanese Patent Application Laid-Open No. 8-157261

[0010] Patent Document 4: Japanese Patent Application Laid-Open No. 8-157262 Summary of the invention

[0011] Problems to be solved by the invention

[0012] In the semiconductor manufacturing device heaters of Patent Documents 1 and 2, if current leaks from the heating element to the wafer, or if current leaks from the electrostatic electrode to the wafer, the wafer may be damaged. Therefore, it is preferable to control the volume resistivity of the AlN ceramic substrate to a high value (e.g., 7×10 8Ωcm or more). However, the volume resistivity of the AlN ceramic matrix sometimes fluctuates due to the influence of impurities, making it difficult to control the volume resistivity. In particular, the AlN ceramic matrix sometimes contains O, C, Ti, Ca, and Y as impurity elements, and it is still unknown what effect these elements have on the volume resistivity.

[0013] In addition, the AlN ceramic matrix of Patent Documents 3 and 4 contains Ti and Ca, but due to the excessive amount of Ti, a very low volume resistivity (2 to 6×10 -5 Ωcm) of the TiN phase, there is a problem that the volume resistivity of the entire AlN ceramic matrix decreases.

[0014] The present invention is proposed to solve such a problem, and its main purpose is to provide a heater for a semiconductor manufacturing device using an AlN ceramic substrate with a high volume resistivity at high temperatures even if the AlN ceramic substrate contains O, C, Ti, Ca, and Y as impurity elements.

[0015] Solution to the problem

[0016] The semiconductor manufacturing device heater of the present invention is a semiconductor manufacturing device heater in which a heating element is buried in an AlN ceramic substrate.

[0017] The AlN ceramic matrix contains O, C, Ti, Ca, and Y as impurity elements and an yttrium aluminate phase as a crystal phase, with a Ti / Ca mass ratio of 0.13 or more, and no TiN phase is confirmed in an XRD spectrum measured using CuKα rays.

[0018] In the heater for semiconductor manufacturing equipment, even if the AlN ceramic matrix used contains O, C, Ti, Ca, and Y as impurity elements, it has a high volume resistivity at high temperature. The reasons for this are examined as follows. If Ca is dissolved in the yttrium aluminate phase (such as Y4Al2O9 (YAM), YAlO3 (YAL), etc.), the divalent Ca will replace the trivalent Y, thereby generating oxygen deficiency due to the valence balance relationship, increasing the oxygen ion conduction path, and reducing the volume resistivity. On the other hand, if Ti is dissolved in the yttrium aluminate phase, the tetravalent Ti will replace the trivalent Al, thereby filling the oxygen deficiency due to the valence balance relationship, and reducing the oxygen ion conduction path. If the mass ratio of Ti / Ca is greater than 0.13, it can be considered that since Ti will appropriately suppress the increase in the oxygen ion conduction path caused by Ca, it can improve the volume resistivity of the AlN ceramic matrix at high temperature.

[0019] In addition, if there is too much Ti in the AlN ceramic matrix, TiN will be generated. The volume resistivity of TiN at room temperature is 2 to 6×10 -5Ωcm, which is about 1.1 times its volume resistivity at room temperature at 600°C (Document 1: Journal of the Japanese Ceramics Association Academic Papers, Vol. 99, No. 4, pp286-291 (1991), Document 2: Electrical Theory A, Vol. 114, No. 12, pp886-891 (1994)). That is, TiN is a compound with extremely low volume resistivity at both room temperature and high temperature. Therefore, in order to make the AlN ceramic matrix have a higher volume resistivity at high temperature, it is preferably free of TiN phase. In addition, if TiN is generated, it is easy to cause insulation breakdown and the corrosion resistance will also be reduced. Therefore, from this point of view, it is also preferred that the AlN ceramic matrix does not contain TiN phase. The XRD spectrum of the TiN phase is published in JCPDS38-1420. If the TiN phase is not confirmed in the XRD spectrum of the AlN ceramic matrix, the decrease in volume resistivity caused by TiN is suppressed, so the volume resistivity of the AlN ceramic matrix at high temperature can be improved, and the insulation breakdown and corrosion resistance caused by TiN can be suppressed. It should be noted that the XRD spectrum is measured using CuKα rays (more specifically, measured using CuKα rays under the conditions of tube voltage 40kV and tube current 40mA).

[0020] It should be noted that the TiN phase may exist in the form of a phase in which Al is solid-dissolved in TiN. However, even in this case, the volume resistivity is extremely low, and it is considered that there is a possibility of causing insulation breakdown and a decrease in corrosion resistance.

[0021] The mass ratio of Ti / Ca in the AlN ceramic matrix is ​​preferably 0.13 to 0.5. The Ti content of the AlN ceramic matrix is ​​preferably 18 mass ppm to 95 mass ppm. The AlN ceramic matrix preferably contains YAM and YAL, in which case the mass ratio of YAM / YAL is preferably 2.8 to 5.3. The mass ratio of O / C in the AlN ceramic matrix is ​​preferably 48 to 65.

[0022] The heater for semiconductor manufacturing equipment of the present invention can be made, for example, as follows: using a mixed powder of AlN raw material powder containing O, C, Ti, and Ca as impurity elements and Y2O3 powder as a sintering aid, burying a heating element inside and forming it, thereby making a molded body, and sintering the molded body. Preferably, the mass ratio of O / C in the AlN raw material powder is 20 to 30, and the mass ratio of Ti / Ca is 0.13 or more. If so, the AlN ceramic matrix after sintering the AlN raw material powder using Y2O3 powder as a sintering aid can easily become the above-mentioned AlN ceramic matrix. Such AlN raw material powder can be obtained by adding appropriate amounts of C, TiO2, and CaO to Al2O3 powder containing O, C, Ti, and Ca as needed to obtain a powder, and nitriding and oxidizing the obtained powder. The AlN raw material powder preferably contains 0.70 to 0.75 mass % of O, 220 to 380 mass ppm of C, 18 to 95 mass ppm of Ti, and 150 to 250 mass ppm of Ca.

[0023] In the heater for semiconductor manufacturing equipment of the present invention, the volume resistivity of the AlN ceramic substrate at 540°C is preferably 1.0×10 9 In this way, the leakage current from the heating element to the wafer mounted on the AlN ceramic base can be sufficiently reduced.

[0024] In the heater for semiconductor manufacturing equipment of the present invention, the bending strength of the AlN ceramic substrate is preferably 300 MPa or more, more preferably 310 MPa or more, which is sufficient strength required as a structural member for semiconductor manufacturing equipment.

[0025] In the heater for semiconductor manufacturing equipment of the present invention, the thermal conductivity of the AlN ceramic substrate is preferably 170 W / m·K or more. In this case, the thermal uniformity of the wafer mounted on the AlN ceramic substrate is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a longitudinal sectional view schematically showing the structure of the electrostatic chuck heater 10 .

[0027] Figure 2 This is a graph showing the relationship between the O / C mass ratio and the volume resistivity.

[0028] Figure 3 This is a graph showing the relationship between the Ti / Ca mass ratio and the volume resistivity.

[0029] Figure 4 This is a graph showing the relationship between the YAM / YAL mass ratio and the volume resistivity.

[0030] Figure 5This is a graph showing the XRD pattern of the AlN sintered body of Experimental Example 1.

[0031] Figure 6 This is a graph showing the XRD spectrum of the AlN sintered body of Experimental Example 7.

[0032] Explanation of symbols

[0033] 10: electrostatic chuck heater, 12: ceramic substrate, 12a: wafer mounting surface, 14: heating element, 16: electrostatic electrode, W: wafer. DETAILED DESCRIPTION

[0034] Below, while referring to the attached Figure 1 Preferred embodiments of the present invention will be described below. Figure 1 It is a longitudinal sectional view schematically showing the structure of the electrostatic chuck heater 10 .

[0035] The electrostatic chuck heater 10 is an example of a heater for a semiconductor manufacturing apparatus according to the present invention, and includes a ceramic base 12 , a heating element 14 , and an electrostatic electrode 16 .

[0036] The ceramic substrate 12 is a disk component made of AlN, and its diameter is, for example, 200 to 450 mm. The upper surface of the ceramic substrate 12 becomes a wafer mounting surface 12a for mounting the wafer W. The ceramic substrate 12 is a substrate with AlN as the main component, but contains O, C, Ti, Ca, and Y as impurity elements, and contains yttrium aluminate phase as a crystalline phase, and the mass ratio of Ti / Ca is greater than 0.13, and no TiN phase is confirmed in the XRD spectrum. Whether the TiN phase is confirmed in the XRD spectrum is determined by comparing the XRD spectrum of the ceramic substrate 12 with all the peaks of the TiN phase. The mass ratio of Ti / Ca in the ceramic substrate 12 is preferably greater than 0.13 and less than 0.5. The Ti content of the ceramic substrate 12 is preferably greater than 18 mass ppm and less than 95 mass ppm. The ceramic substrate 12 preferably contains YAM and YAL as yttrium aluminate phases, in which case the mass ratio of YAM / YAL is preferably greater than 2.8 and less than 5.3. The mass ratio of O / C in the ceramic base 12 is preferably 48 to 65.

[0037] The heating element 14 is embedded in the ceramic substrate 12. The heating element 14 is a metal coil wired in a predetermined pattern on the entire surface of the wafer mounting surface 12a by a one-stroke method. The heating element 14 is not limited to a metal coil, and can also be in various forms such as a strip, a mesh, and a sheet. As a material for the heating element, a high melting point conductive material such as Mo, W, and Nb is preferred.

[0038] The electrostatic electrode 16 is embedded in the ceramic substrate 12. The electrostatic electrode 16 is disposed between the wafer mounting surface 12a and the heating element 14. The shape of the electrostatic electrode 16 is not particularly limited, and may be a punched metal in addition to a plane shape or a mesh shape. The material of the electrostatic electrode 16 is preferably a high melting point conductive material such as Mo, W, or Nb.

[0039] Next, an example of using the electrostatic chuck heater 10 is described. First, the electrostatic chuck heater 10 is set in a chamber not shown in the figure. Then, the chip W is placed on the chip mounting surface 12a of the electrostatic chuck heater 10, and a voltage is applied to the electrostatic electrode 16 to generate an electrostatic adsorption force such as Johnson-Rabbeck between the electrostatic electrode 16 and the chip W, thereby adsorbing and fixing the chip W on the chip mounting surface 12a. In addition, the external terminal is connected to a metal coil serving as a heating element 14 and a voltage is applied to the heating element 14 to generate heat, thereby heating the chip W to a predetermined temperature. In this state, various processes required for manufacturing semiconductor chips are applied to the chip W. After the processing is completed, the application of voltage to the electrostatic electrode 16 and the application of voltage to the heating element 14 are stopped, and the chip W is removed from the chip mounting surface 12a.

[0040] Next, a manufacturing example of the electrostatic chuck heater 10 is described. First, an AlN raw material powder containing O, C, Ti, and Ca as impurity elements is prepared. The AlN raw material powder preferably has an O / C mass ratio of 20 to 30 and a Ti / Ca mass ratio of 0.13 or more. Such an AlN raw material powder can be obtained by adding appropriate amounts of C, TiO2, and CaO to an Al2O3 powder containing O, C, Ti, and Ca as needed to obtain a powder, and nitriding and oxidizing the obtained powder. The AlN raw material powder preferably contains 0.70 to 0.75 mass% O, 220 to 380 mass ppm C, 18 to 95 mass ppm Ti, and 150 to 250 mass ppm Ca.

[0041] Next, Y2O3 powder as a sintering aid is added to the prepared AlN raw material powder and mixed to prepare a mixed powder, and the mixed powder is formed into particles by spray drying. Y2O3 is added in a manner of 4.5 to 5.5 mass % relative to the entire mixed powder. As a mixing method, wet mixing using an organic solvent can be adopted, and dry mixing such as ball milling, vibration milling, dry bag mixing, etc. can also be adopted.

[0042] Next, using the particles of the mixed powder, the heating element 14 and the electrostatic electrode 16 are buried inside and formed to produce a formed body. Then, the formed body is sintered to make an AlN sintered body. Thus, the electrostatic chuck heater 10 is obtained. The sintering method is not particularly limited, for example, hot pressing sintering can be used. In the case of hot pressing sintering, it is preferred that the maximum temperature during sintering (sintering temperature) is set to 1700-1900°C, the holding time at the sintering temperature is set to 0.5-100 hours, the pressing pressure is set to 5-50MPa, and the atmosphere is set to a nitrogen atmosphere or a vacuum atmosphere (for example, 0.13-133.3Pa).

[0043] According to the electrostatic chuck heater 10 of the present embodiment described above, since the mass ratio of O / C, the mass ratio of Ti / Ca and the mass ratio of YAM / YAL are all within the appropriate numerical range, the volume resistivity of the ceramic substrate 12 is improved, and the leakage current from the heating element 14 and the electrostatic electrode 16 to the chip mounted on the chip mounting surface 12a of the ceramic substrate 12 can be reduced.

[0044] It should be noted that the present invention is not limited to the above-mentioned embodiments, and it goes without saying that the present invention can be implemented in various ways as long as it falls within the technical scope of the present invention.

[0045] For example, in the above embodiment, the electrostatic chuck heater 10 is exemplified as the heater for a semiconductor manufacturing apparatus of the present invention, but the electrostatic electrode 16 may be omitted or replaced with an RF electrode.

[0046] Example

[0047] [Experimental Examples 1 to 11]

[0048] For each experimental example, the AlN raw material powder shown in Table 1 was prepared. The mass of the impurity elements contained in the AlN raw material powder was determined as follows. The mass analysis of the impurity elements was implemented in accordance with JIS R1675. Specifically, for oxygen, about 0.05 g of the sample was put into a Ni capsule, put into a graphite crucible, heated and burned, extracted in the form of CO, and quantified by a non-dispersive infrared detector. For carbon, about 0.5 g of the sample was taken, heated and burned after adding a combustion aid (Sn, etc.), and the generated CO+CO2 was quantified by a non-dispersive infrared detector. For metal impurities, about 1 g of the sample was taken, a predetermined amount of nitric acid, hydrochloric acid, and hydrogen peroxide were added, and the solution after heating and dissolution was measured by ICP emission analysis.

[0049] Y2O3 powder as a sintering aid is added to the prepared AlN raw material powder, and mixed by a ball mill to make a mixed powder, and the mixed powder is granulated by spray drying. Y2O3 is added in a manner of 5% by mass relative to the entire mixed powder. Next, a disc-shaped molded body is made using the particles of the mixed powder. Then, the molded body is hot-pressed to make an AlN sintered body. In the hot-pressing sintering, the maximum temperature (firing temperature) during firing is set to 1850-1890°C, the holding time at the firing temperature is set to 2 hours, the pressing pressure is set to 20MPa, and the atmosphere is set to a nitrogen atmosphere. The mass of the impurity elements contained in the obtained AlN sintered body, the mass of YAM, and the mass of YAL are measured.

[0050] The mass of impurity elements in the AlN sintered body is measured by the same method as the mass of impurity elements in the AlN raw material powder. The mass of YAM and YAL is measured as follows. First, the high-angle side of 10deg to 120deg or more is accurately measured by powder X-ray diffraction to obtain an XRD spectrum, and the obtained XRD spectrum is used to identify the crystalline phase. The identified crystalline phase is assumed to perform Rietveld analysis to calculate the quantitative value of each crystalline phase. The volume resistivity of the AlN sintered body at 540°C is measured as follows. After heating the sample (50mm×50mm×1mm) made of Ag paste printed electrode parts to 540°C, the current value after 1 minute when 1kV voltage is applied is measured to obtain the volume resistivity. The flexural strength is measured by a four-point bending test in accordance with JIS R1601. The thermal conductivity is measured at room temperature by a laser flash method in accordance with JIS R1611. Their results are shown in Table 2. In addition, the relationship between the O / C mass ratio and the volume resistivity is shown in Figure 2 The relationship between the Ti / Ca mass ratio and the volume resistivity is shown in Figure 3 The relationship between the YAM / YAL mass ratio and the volume resistivity is shown in Figure 4 .

[0051] In X-ray diffraction, about 0.5 g of powder was measured by Bruker AXS D8 ADVANCE. The measurement conditions were: CuKα ray source, tube voltage 40 kV, tube current 40 mA. The measurement results were subjected to Rietveld analysis to identify and quantify the crystal phase. The results are shown in Figure 5 , Figure 6 and Table 2. Figure 5 and Figure 6 The graph shows the XRD patterns of Experimental Examples 1 and 7. The crystal phases identified from the XRD patterns of Experimental Examples 1 and 7 are AlN, YAM, and YAL, and no TiN is confirmed. Although the XRD patterns of Experimental Examples 2 to 6, 8, and 9 are omitted, the same results are obtained.

[0052] [Table 1]

[0053]

[0054] [Table 2]

[0055]

[0056] The AlN sintered bodies of Experimental Examples 1 to 9 contain O, C, Ti, Ca, and Y as impurity elements, and contain YAM and YAL as crystalline phases, with a Ti / Ca mass ratio of 0.13 or more, and no TiN phase is confirmed in the XRD spectrum. The volume resistivity of these AlN sintered bodies at 540°C is as high as 1.0×10 9 (=1.0E+09)(Ωcm) or more. Figure 1 When the ceramic substrate 12 of the electrostatic chuck heater 10 shown in the figure is used, the leakage current from the heating element 14 and the electrostatic electrode 16 to the wafer W placed on the wafer placement surface 12a can be reduced. It should be noted that in the AlN sintered bodies of Experimental Examples 1 to 9, the mass ratio of Ti / Ca is 0.13 or more and 0.5 or less, the Ti content is 18 mass ppm or more and 95 mass ppm or less, the mass ratio of YAM / YAL is 2.8 or more and 5.3 or less, and the mass ratio of O / C is 48 or more and 65 or less.

[0057] In contrast, the volume resistivity of the AlN sintered bodies of Experimental Examples 10 and 11 at 540°C was 4.5×10 8 [Ωcm] or less. In Experimental Examples 10 and 11, in particular, the mass ratio of Ti / Ca is outside the appropriate range, which is considered to be the reason for the decrease in volume resistivity. That is, in Experimental Examples 10 and 11, since the mass ratio of Ti / Ca is as low as 0.08 and 0.07, it can be considered that the situation where Ca solid dissolves into YAM and YAL and increases the oxygen ion conduction path is better than the situation where Ti solid dissolves into YAM and YAL and reduces the oxygen ion conduction path, thereby reducing the volume resistivity. In Experimental Example 10, the Ti content is outside the appropriate range, the mass ratio of YAM / YAL is outside the appropriate range, the mass ratio of O / C is outside the appropriate range, etc., which are also considered to be the reasons for the decrease in volume resistivity. In Experimental Example 11, the Ti content is outside the appropriate range, the mass ratio of O / C is outside the appropriate range, etc., which are also considered to be the reasons for the decrease in volume resistivity.

[0058] In addition, the bending strength of the AlN sintered bodies of Experimental Examples 10 and 11 was as high as 353 MPa and 328 MPa, and the bending strength of the AlN sintered bodies of Experimental Examples 1 to 9 was also 300 MPa or more (specifically, 310 MPa or more), which is substantially the same high value as Experimental Examples 10 and 11. Furthermore, the thermal conductivity of the AlN sintered bodies of Experimental Examples 10 and 11 was as high as 190 W / m·K and 180 W / m·K, and the thermal conductivity of the AlN sintered bodies of Experimental Examples 1 to 9 was also 170 to 180 W / m·K, which is substantially the same high value as Experimental Examples 10 and 11.

[0059] Among the above-mentioned Experimental Examples 1 to 11, Experimental Examples 1 to 9 correspond to the embodiments of the present invention, and Experimental Examples 10 and 11 correspond to comparative examples.

[0060] This application claims priority based on Japanese Patent Application No. 2018-20637 filed on February 8, 2018, the entire contents of which are incorporated herein by reference.

[0061] Industrial Applicability

[0062] The present invention can be used in heaters for semiconductor manufacturing equipment, such as electrostatic chuck heaters and ceramic heaters.

Claims

1. A heater for semiconductor manufacturing equipment, wherein a heating element is buried in an AlN ceramic substrate. An RF electrode is embedded in the AlN ceramic matrix. The AlN ceramic matrix contains O, C, Ti, Ca, and Y, and contains an yttrium aluminate phase as a crystalline phase, and the mass ratio of Ti / Ca is greater than 0.

13. The Ti content of the AlN ceramic substrate is 18 mass ppm or more and 95 mass ppm or less.

2. The heater for semiconductor manufacturing equipment according to claim 1, In the XRD pattern measured using CuKα radiation, no TiN phase was confirmed.

3. The heater for semiconductor manufacturing equipment according to claim 1 or 2, The mass ratio of Ti / Ca is less than 0.

5.

4. The heater for semiconductor manufacturing equipment according to claim 1 or 2, The AlN ceramic matrix contains YAM and YAL, and the mass ratio of YAM / YAL is greater than or equal to 2.8 and less than or equal to 5.

3.

5. The heater for semiconductor manufacturing equipment according to claim 1 or 2, The mass ratio of O / C in the AlN ceramic matrix is ​​48 to 65.

6. The heater for semiconductor manufacturing equipment according to claim 1 or 2, The volume resistivity of the AlN ceramic matrix at 540°C is 1.0×10 9 Ωcm or more.

7. The heater for semiconductor manufacturing equipment according to claim 1 or 2, The bending strength of the AlN ceramic substrate is greater than 300 MPa.

8. The heater for semiconductor manufacturing equipment according to claim 1 or 2, The thermal conductivity of the AlN ceramic matrix is ​​greater than 170 W / m·K.

Citation Information

Patent Citations

  • Aluminum nitride sintered compact and its production

    JP1996157261A

  • Aluminum nitride sintered compact and its production

    JP1996157262A

  • Aluminum nitride substrate and method of manufacturing the same

    JP2005281046A

  • Heating device

    JP2008153194A

  • Occupant protection device for vehicle

    JP2018020637A